ANALISIS KEPUASAN PEMUSTAKA TERHADAP KUALITAS JASA LAYANAN MENGGUNAKAN METODE LIBQUAL+TM - , Rahayuningsih, Dr. Partini, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
User satisfaction is the benchmark of libraryâs success. Users satisfaction level can be measured by using LibQUAL+TM, by analyzing three dimensions of libtaty services that is Affect of Service, Information Control and Library as Place. This research is intended to know the usersâsatisfaction level in Sanata Dharma University Library (USDL). LibQuaL calculate the score given by the users for each question relating to three categories, that is, perception, minimum expectation and ideal expectation. User satisfaction is measured from Adequacy Gap (AG) and Superioty Gap (SG). This gap is generated from the difference between perception, minimum expectation and ideal expectation. This research is using mixed method and sequential explanatory strategy as research strategy. Research population are the students visiting USDL.Based on Isaac and Michael able, sample is drawn for 255 students.These sample is chosen by using Simple Random Sampling. Qualitative data is gathered from 12 âMitra Perpustakaanâ members, as informants. Data analysis is done by SPSS for Windows 20 version. Statistical analysis used to test the hypothesis is Mean Difference T-Test, using SPSS for Windows2000, as for qualitative data analysis used is categorical approach. The research result shows that library user are âquite satisfiedâ and they rate the quality of USD library services as âgoodâ or in the tolerance zone. LibQual+TMdimension which give the highest contribution to user satisfaction is Affect of Service where librarian courtesy, user friendly, ability to convey services according to library service hours, competency and assistance given for the library users to retrieve informasion. The dimension which gave less contribution to library users satisfaction is Information Control and Library as Place. Library users are ânot satisfiedâ with theadequacy on the number of the printed books. Library users are âquite satisfiedâ, with the lowest score on title availability for electronic books and journals, connectivity speed for hotspot facility to retrieve information, quiet space for study, library design which inspire study and creativity.